Accuracy Of Statistical Indicators In Kashan University Of Medical Sciences Hospitals In March 2009-August 2010 - Mehrdad Farzandipor; Mehdi Shaeri; Fatemeh Rangraz Jeddi (Tehran University of Medical Sciences, 2012)
Background and Aim: Nowadays, Information conduct health care system and its substantiation depend on available correct data and reliable information. This study was performed to determine the accuracy rate of statistical indicators in Kashan educational hospitals. Materials and Methods: This was a cross-sectional descriptive study carried out in March2009- August 2010. Data(the items that need for evaluate of each indicator) were gathered with self-designed checklist. The accuracy of items and hospital indicators were compared with items and indicators that researcher had gathered or calculated. Data(frequency and percent) was presented with descriptive statistical method. Results: Findings showed that maximum rate of accuracy was found in gross death percentage(68%), and minimum rate was found for the average bed count(24%). The accuracy rates of other indicators were: bed occupancy percentage(39%), bed turn over rate(47%), and bed occupancy average(61%). Net death percentage and bed turn over interval both were(49%). Totally, the accuracy of hospital indicators were 53% which was in a moderate level. Conclusion: The accuracy of hospital indicators is low. Use of monitoring methods for improvement of its accuracy is recommended.